Development and validation of MRI-based model for the preoperative prediction of macrotrabecular hepatocellular carcinoma subtype - Ismail Bilal Masokano; Yigang Pei; Juan Chen; Wenguang Liu; Simin Xie; Huaping Liu; Deyun Feng; Qiongqiong He; Wenzheng Li (Insights into Imaging, 2022)
Key points Clinicoradiologic model has a good performance in diagnosing MTHCC. In validation set, models 2 and 3 did not significantly improve predictive performance compared to clinicoradiologic model. Clinicoradiologic model yielded higher clinical benefit at MTHCC threshold probability of 10%. Clinicoradiologic model is as beneficial as model 3, yet simpler and easier.